WAKAF PENJAGAAN KESIHATAN: KAJIAN KES DI HOSPITAL WAQAF AN-NUR: Healthcare Waqf: Case Study in Hospital Waqaf An-Nur - Mohamed @ Haji Daud, Norizah; Ab Rahman, Asmak (Jurnal Syariah, 2017)
Waqf is a unique form of welfare in Islam because it is worship that combines both spiritual and material aspects. Waqf plays a major role in helping the government to provide services such as health and education to the society. This could be clearly seen during the golden age of Islam at the time of the Ottoman Empire. This article discusses the role and contribution played by the Waqf at Waqaf An-Nur Hospital (HWAN) in providing healthcare services to the local community. Health is a necessity for all, but for the poor and low-income people, health becomes a very expensive thing. The implementation of this hospital is seen as an alternative for low-income people, especially for the poor and the needy to receive medical treatment, regardless of race and religion. Data were collected by interviewing the patients who had received treatment at HWAN, as well as the Operations Manager and staff of HWAN. Observation was also employed to collect data. Data from the interviews were analysed using content analysis based on themes. The results from this study show that Waqaf An-Nur Hospital imposed fees and charges for the healthcare services provided to patients at a lower rate. Waqf is an alternative to help ease the financial burden of society in terms of health and medical care because the cost of treatment is increasing from year to year.